STRATEGI KOMUNIKASI PT ERTRI INDONESIAN DALAM MENJAGA EKSISTENSI SEBAGAI DIGITAL AGENCY - Mukka Pasaribu; Haviansha Siregar (Universitas Prof. Dr. Moestopo (Beragama), 2019)
The purpose of this research is to determine the existence and inhibiting factors of PT Ertri Indonesia and how the communication strategy of PT Ertri Indonesia in maintaining the existence of the Digital Agency. The theory used by New Media, and Mouth to Mouth (WoM). The research approach used is qualitative and uses the post positivism paradigm. To become a Digital Advertising service provider, PT Ertri Indonesia must draft and conduct tenders in accordance with the instructions given by the client. Based on the results of the study show that providing trust by producing client needs internally and good access to communication to demand client needs is the main strategy of PT Ertri Indonesia found in this study. In addition, PT Ertri Indonesia needs mouth to mouth to get new clients from the recommendations of old clients who have used PT Ertri Indonesias services.